FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KARYAWAN DALAM PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) PADA AREA PENAMBANGAN TAMBANG BAWAH TANAH PT. BUKIT ASAM (PERSERO) TBK, UNIT PERTAMBANGAN OMBILIN, SAWAHLUNTO, SUMATERA BARAT - Ricci Rahman; Rijal Abdullah; Yunasril Yunasril (Departemen Teknik Pertambangan FT UNP, 2015)
The purpose of the health and safety program K3 in the company is to keep employees good in work and anticipate an accident. Unsafe action and unsafe condition are the direct caused of the accident happen. It can anticipate by improve the SMK3 management sistem. Knowledge, attitude, and the act of employees are the factors that influence the management system woking. Well, this research purpose to know the K3 Management Sistem working or not.This research is could be classified as to the kind of research of correlational. The population on this research is all employees of which are at work unit and means of mining engineering PT.Bukit Asam (Persero ) Tbk, UPO that total about 22. Data collection by using a questionnaire that has been tested validity and reliabilitasnya. Furthermore, the data mixed with use a computer program spss 15.0. version.The results from this research is there are significant relationship between knowledge with the application of the K3, between the attitude with the application of the K3, between the act of an employee with the application of the K3. It Can be concluded that from three factors are having a significant relation toward K3 applicate on PT .Bukit Asam (Persero) Tbk, UPO, Sawahlunto, of West Sumatra. In this case, the company should be enrich the employees knowledge about K3, make a lot of guidelines about the health and safety of employment in the area by mining, and the socialization regularly and sustainable covering all aspects.